153 DEVELOPMENTAL CHANGES IN T-HELPER BIAS IN MURINE DISEASE MODELS. (1st January 2006) - Staley, E. M.; Dimmitt, R. A.; Chuang, G.; Rygiel, S. D.; Lorenz, R. G.
Abstract : Background: Since the discovery of T helper subsets in 1986, T cells have been classified as TH1 or TH2 on the basis of their cytokine secretion profile. Th1 responses are stimulated by intracellular pathogens and produce high levels of cytokine IFN-g. Dysregulation of the Th1 response has been linked to multiple sclerosis and susceptibility to influenza. Th2 responses are stimulated by extracellular pathogens and produce high levels of IL-4, and dysregulation is linked to development and progression of asthma. Mouse strains have been shown to have predispositions toward Th1 or Th2 responses, making certain strains more suitable models for disease studies. It is the purpose of this study to determine the time in development that such biases initiate in the C57BL/6 (TH1) and BALB/c (TH2) strains. Methods: Splenocytes were harvested from adult (6-8 week) and aged (> 6 months) mice and seeded in 96-well plates previously coated with aCD3 stimulating antibody or isotype control. Supernates were collected 4 days post stimulation and stored at 280. Cytokine ELISAs were performed as per manufacturer's instructions using assays from Biolegend (San Diego, CA), and cytokine concentrations were determined using a VersaMax plate-reader and the Soft-Max Pro analysis program. Results: At 96 hours post-stimulation the TH1 biased strain (B6) was producing 82.51 ng/mL of IFN-g (6 2.62 ng/mL) while the TH2-biased animals (BALB/c) were producing 40.54 ng/mL IFN-g (6 12.61 ng/mL). At the same time point TH1 animals produced 1.80 ng/mL IL-4 (6 0.3 ng/mL), and TH2-biased animals produced 3.49 ng/mL IL-4 (6 1.02 ng/ml). The stimulation with isotype control has been shown to produce no significant splenocyte stimulation. Conclusions: It has been shown in our lab as well as others that adult B6 and BALB/c mice express a bias in T helper response. Future experiments in our lab will revolve around discovering the stage of development in which the bias initiates. In future studies splenocytes from newborn and early adolescent mice will be analyzed for cytokine expression upon stimulation with a-CD3. Implications: Murine T-helper bias has lead to strain-specific models of disease. The progression of bias development could be of great use to pediatric research specifically to allow for more accurately designed disease models.